Práticas e representações sociais sobre reprovação: um estudo no curso de Engenharia Elétrica da Universidade Federal de Uberlândia - Araújo, Léia Souza Alves de (2003)
The research “Practices and Social Representations on Failure: A study of the Electrical Engineering Course of the Federal University of Uberlândia -UFU was developed in tlie Masters in Education Program at the Federal University of Uberlândia, lfom 2001 to 2002. The objective of the-study was to analyze social representation of the phenomenon of failure in the teaching-leaming process in an undergraduate course of UFU. The study focused on understanding evaluations and failure, their forms, meaning and function lfom the perspective of research participants - teachers and students. The study also sought to analyze the relationship between social representations of this phenomenon and the repercussions of the interactions between teachers and students in the teaching-leaming process as it perpetuates or transforms educational practice in the Electrical Engineering Course at UFU. The research is a qualitative study having, nonetheless, quantitative data that served as a basis for selecting the participants who were interviewed for the study and also afforded systematic presentation of failures recorded from 1997 to 2001 of the two majors in the Electrical Engineering Programs: Electronics and Eletrotechniques. The participants were eiglit students who had taken the five disciplines tliat had the higliest rates of failure in the period of time selected for the study: Electromagnetism, Material Mechanics, Electrical Circuitiy 1, Electrical Materials 1 and General Physics 3. Three faculty members who teach these disciplines also participated in the study. In the interviews that were conducted, however, the focus was not exclusively on the five disciplines mentioned in that the goal was to understand and analyze the complexity of the factors that caused failure without singling out a given discipline. The research posited that there were ideas, stances, behaviors that are shared and produced by the group and that circulated among the participants and thus perpetuated failure, which is also a characteristic of social representation. To provide a better understanding of failure in these specific majors it was important to review the historical background of the School of Electrical Engineering - UFU. To this end teaching and a general profile of graduates in Electrical Engineering was also discussed. An analysis of the role of evaluation in the leaming process was also studied. The analyses point to the fact that facing the problem of failure in Electrical Engineering - UFU, as well as at otlier courses of engineering at otlier mstitutions would benefít the teaching-leaming process as well as improving the quality of teachers in these programs. It also implies the need to understand the global and dynamic process in the day-to-day fimctioning of the program. In addition there is need for the group to face existing problems as well as negative views, authoritarian stances and conservative practices that sustain and perpetuate failure, leading to passive acceptance of the current situation. However, it should be recalled that social representations contain the elements that also transform and lead to cliange in the existing reality.